Student Teachers’ Video-Assisted Collaborative Reflections of Socio-Emotional Experiences During Teaching Practicum - Näykki, Piia; Laitinen-Väänänen, Sirpa; Burns, Eila (Frontiers in Education, 2022)
This study explores video as a tool for student teachers in reflecting upon their own teaching practice. The particular interest is in exploring, what kind of socio-emotional experiences did the student teachers describe during the video-assisted collaborative reflection and what benefits student teachers experienced through the video-assisted collaborative reflections? The study implements a video-observation model (Participatory and Empowering Video Analysis- model, PEVA™) developed for a professional teacher education programme and investigates the model from student teachers’ perspective. The participants are student teachers in an international professional teacher education programme (n=24) at a university of applied sciences. Student teachers video recorded their own teaching sessions displaying their work in different roles: teacher-led content specific instructions, group working sessions and individual student guidance and tutoring sessions. Student teachers were advised to annotate their own videos with a video-reflection tool by focusing on socio-emotional interactions, non-verbal elements of interaction and moments, where students felt successful and empowered. In addition to self-reflection, videos were viewed and annotated by a peer student and a teacher educator. After the phases of reviews and annotations (self-, peer-, and teacher annotations), an hour-long collaborative reflective feedback discussion was held either face-to-face or online. These sessions were facilitated by the teacher educator, involving the videoed student and the reviewing peer. Video annotation data was transcribed, and, in addition, the student teachers' reflective writings (54 pages) and teacher educators’ notes of the reflective feedback sessions (20 pages) were used as data. The results of this study indicate that student teachers viewed the video reflection process as helpful in making socio-emotional experiences visible and tangible. The video annotation tool was recognized as useful for indicating socio-emotional experiences and making them more concrete thus resources for reflection. A combination of own, peer’s and teachers’ annotations functioned as a collaborative tool for increasing awareness of different socio-emotional experiences. By observing videos of their own teaching as well as teaching videos of their peers, student teachers were able to evaluate teaching situations holistically and observe connections of their own socio-emotional behaviours to their students.